PERAN HOME INDUSTRI DALAM MENINGKATKAN EKONOMI KELUARGA (STUDI KASUS HOME INDUSTRY KERIPIK - Ananda, Riski; ", Ashaluddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Research conducted in September 2015 until December 2015, in the village stronghold gadang jorong koto nan IV Payakumbuh city aims to find outHow do home activities chips industry is able to survive and any ways in which the home industry to improve competitiveness so that it continues to rise. The method used is a qualitative method. The subject is the owner of home industry is already running a home industry for 5 to 20 years. The data obtained are described qualitatively. The results showed thatin sustaining capital and increase capital carried out by the owner of home industry is good, by recording a careful and always counted the goods into the goods out. To maintain and improve the existence of labor is correct. Only in terms of marketing is not good because it is still up to pengampas.Keywords: Home Industry, Adaptation and Social Networking